Efficient FPGA Hardware Reuse in a Multiplierless Decimation Chain - Guillermo A. Jaquenod; Javier Valls; Javier Siman (International Journal of Reconfigurable Computing)
In digital communications, an usual reception chain requires many stages of digital signal processing for filtering and sample rate reduction. For satellite on board applications, this need is hardly constrained by the very limited hardware resources available in space qualified FPGAs. This short paper focuses on the implementation of a dual chain of 14 stages of cascaded half band filters plus 2 : 1 decimators for complex signals (in-phase and quadrature) with minimal hardware resources, using a small portion of an UT6325 Aeroflex FPGA, as a part of a receiver designed for a low data rate command and telemetry channel.